If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + -58 = 8x + 44 Reorder the terms: -58 + 25x = 8x + 44 Reorder the terms: -58 + 25x = 44 + 8x Solving -58 + 25x = 44 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -58 + 25x + -8x = 44 + 8x + -8x Combine like terms: 25x + -8x = 17x -58 + 17x = 44 + 8x + -8x Combine like terms: 8x + -8x = 0 -58 + 17x = 44 + 0 -58 + 17x = 44 Add '58' to each side of the equation. -58 + 58 + 17x = 44 + 58 Combine like terms: -58 + 58 = 0 0 + 17x = 44 + 58 17x = 44 + 58 Combine like terms: 44 + 58 = 102 17x = 102 Divide each side by '17'. x = 6 Simplifying x = 6
| 2x+21=19 | | -2(4r+1)=-16+6r | | 67-3/4x=21 | | 9+17t-1=6t+34-2t | | 2x+33=75-5x | | 7x+5(x+9)= | | 18x^2y^3+24xy^5= | | 11(t-3)+7t=6(3t+3)-9 | | -4a(3a-5a)=0 | | -3(v-3)=5v+17 | | 5+18a=77 | | 16-4ln(3x)=20 | | 7(x+9)+5x= | | 3y=8x+1 | | 36+6n=-6(1-8n) | | x^2+12=24+x | | x-8.8=6.1 | | 2x+6(-2x-4)=-29-5x | | log[4](-4x)=1 | | 11e-12+9e-16=13e+42 | | 7x+5(x-9)= | | -5x+165=-3x+153 | | -6(-6+4x)=3x-18 | | 44428=974x+17156 | | 97=-7(x-7)-5x | | 2x^2-12x-34=0 | | 15x=9x+24 | | -6(4+6x)=-4x-24 | | 24x^2-40x-56=0 | | 52/7-5/14 | | 18-5x-2=-4 | | 7-(m-2)=12 |